In Vitro Dose Studies on Chitosan Nanoplexes for microRNA Delivery in Breast Cancer Cells - (:unkn) unknown (MARY ANN LIEBERT, INC, 2017)
Changes in microRNA (miRNA) expression levels that play important roles in regulation lead to many pathological events such as cancer. The miR-200 family is an important target in cancer therapy. The aim of this study is to equilibrate endogenous levels between cancer and noncancerous cells to prevent serious side effects of miR-200c- and miR-141-like metastatic colonization. For the first time, the characterization of miR-200c and miR-141 cluster containing chitosan nanoplexes was shown, and the optimization of miRNA expression levels by conducting dose studies in breast cancer cell lines was made. The mean diameter of chitosan/miR-141 and chitosan/miR-200c nanoplexes ranged from 296 to 355 nm and from 294 to 380 nm depending on the N/P ratio, respectively. The surface charge of nanoplexes was positive with zeta potential of +12 to +26 mV. While naked miRNA was degraded after 0 min in a 10% serum-containing medium, chitosan/miRNA nanoplexes were protected for 72 h. During the in vitro cellular uptake study, nanoplexes were observed to be accumulating in the cytoplasm or nucleus. After using different doses for miR-200c, the determined doses are 750, 100, and 750 ng in the MCF-7, MDA-MB-231, and MDA-MB-435 cell lines, respectively. Doses were determined as 100 ng for MDA-MB-231 and 150 ng for MDA-MB-435 to reach endogenous miR-141 levels of MCF-10A. Our results suggest that chitosan nanoplexes for miR-200c and miR-141 are an efficient delivery system in terms of formulation and transfection. As a conclusion, dose studies are important to provide effective treatment with miRNAs.
Keywords: dose; miRNA therapeutics; chitosan; breast; cancer; miR-200c; miR-141; MOLECULAR-WEIGHT; GENE DELIVERY; EXPRESSION; THERAPY; NANOPARTICLES; METASTASIS; GROWTH; NANOCOMPLEXES; COLONIZATION; VECTOR